2006
DOI: 10.1057/palgrave.rlp.5100001
|View full text |Cite
|
Sign up to set email alerts
|

Vacation ownership: Understanding the senior market

Abstract: Tammie J. Kaufmanhas over 25 years of experience in the hotel, restaurant and travel industry. She has worked in all facets of the industry from management to line-employee positions. She has been teaching at Rosen College for four years. Randall Upchurchis professor of timeshare development at Rosen College. Dr Upchurch has over 21 years of experience in the lodging industry. In his present position Dr Upchurch is actively working with the American Resort Development Association to deliver a minor in timeshar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Haylock (1994aHaylock ( , 1994b, Upchurch & Gruber (2002) and Powanga & Powanga (2008) demonstrate that as an accommodation product timeshare has increasingly evolved and influenced shifts in the broader lodging sector within which it is located. Currently timeshare as a product can be found throughout the world in a variety of forms from single holiday flats, luxury condominiums, hotel destination resorts, mixed resorts, and single urban tourist hotels, to cruise ships, boats, villas, yachts and exclusive five star apartments (Kaufman et al, 2006). From precarious beginnings timeshare has emerged as a profitable and dynamic branch of property development and several international corporations have branded the timeshare industry with their expanding scope of development and long-term business planning (Deng, 2013).…”
Section: International Research Trends On Timeshare Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Haylock (1994aHaylock ( , 1994b, Upchurch & Gruber (2002) and Powanga & Powanga (2008) demonstrate that as an accommodation product timeshare has increasingly evolved and influenced shifts in the broader lodging sector within which it is located. Currently timeshare as a product can be found throughout the world in a variety of forms from single holiday flats, luxury condominiums, hotel destination resorts, mixed resorts, and single urban tourist hotels, to cruise ships, boats, villas, yachts and exclusive five star apartments (Kaufman et al, 2006). From precarious beginnings timeshare has emerged as a profitable and dynamic branch of property development and several international corporations have branded the timeshare industry with their expanding scope of development and long-term business planning (Deng, 2013).…”
Section: International Research Trends On Timeshare Industrymentioning
confidence: 99%
“…The development of new market segments or niches for marketing the timeshare product has been another facet of improved marketing for timeshare sales in developed countries where there is much attention to seniors (Kaufman et al, 2006). In addition to marketing issues another important and overlapping cluster of work around timeshare relates to the management of timeshare resorts (Upchurch & Lashley, 2006).…”
Section: International Research Trends On Timeshare Industrymentioning
confidence: 99%
“…The majority of the research has focused on consumer behavior, and the marketing aspects of the vacation ownership industry ( Woodside et al , 1985 ;Weaver and Lawton, 1999 ;Crotts and Ragatz, 2002 ;Rezak, 2002 ;Woods and Clark, 2002 ;Crotts et al , 2005 ;Kaufman et al , 2005 ;McCain et al , 2005 ). Research has explored resort amenities and their utilization by owners ( Kaufman et al , 2006 ;Stringam, 2008 ). Other studies have examined owner satisfaction, niche markets and fi nite geographic markets ( Liu et al , 2001 ; .…”
Section: Review Of the Literaturementioning
confidence: 99%
“…1 With this growth there has been limited research to understand and better defi ne the potential timeshare consumer. Relative to understanding consumer characteristics Kaufman 3 have begun to segment the timeshare market based on age and found that there are indeed signifi cant consumption differences based on the age of a timeshare owner.…”
Section: Introductionmentioning
confidence: 99%